Metastatic Prostate Carcinoma Presenting as Supraclavicular Lymphadenopathy – Is it Unusual? - Ahamed, SH (The Royal College of Surgeons of England, 2006)
Prostate carcinoma presenting initially as supraclavicular lymphadenopathy has been increasingly reported as an uncommon presentation of the disease. The diagnosis is often made on lymph node biopsy as these patients rarely undergo digital rectal examination or serum prostate-specific antigen level measurement as part of their initial investigations. A 74-year-old man presented with supraclavicular lymphadenopathy and subsequently deteriorated with severe shortness of breath associated with venous congestion of the head and neck. The diagnosis of metastatic prostate adenocarcinoma was made only after cervical lymph node biopsy. Following the diagnosis, he was confirmed as having an abnormal prostate on digital rectal examination and a raised serum prostate-specific antigen level. The authors propose that a digital rectal examination and a serum prostate specific antigen level be included in the initial investigation process of male patients with persistent supraclavicular lymphadenopathy. This would prevent delay in diagnosis, allow early intervention and decrease patient morbidity.